Transforming Character Education Through the 4T Program Based on Digital Literacy - Nisa, Fara; Restian, Arina; Zuriah, Nurul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the transformation of character education through the implementation of the 4T program, Qur’anic memorization, Qur’anic reading improvement, Qur’anic comprehension, and Qur’anic value application integrated with digital literacy at SMP MBS Madiun. The research is grounded in the need for Islamic educational institutions to combine Qur’anic values with digital competence to ensure that character formation remains relevant to the demands of the 21st century. A qualitative case study approach was employed to allow an in-depth exploration of character-building practices within both school and boarding environments. The research site was purposively selected across two campuses of SMP MBS Madiun, involving 12 informants consisting of the mudir, school principal, vice principal for student affairs, 4T program teachers, mentor, and parents. Data were collected through semi-structured interviews, direct observations, and documentation, using instruments such as interview guides, checklist-based observation sheets, and field notes. Data analysis followed Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, strengthened by source and technique triangulation. The findings indicate that the digitally supported 4T program effectively strengthens students’ character development in a more systematic, monitored, and measurable manner, particularly in aspects of discipline, Qur’anic reading accuracy, comprehension of values, and implementation of Islamic manners in daily life. The study concludes that integrating Qur’anic values with digital literacy serves as an effective strategy for enhancing character formation in modern Islamic boarding schools.